Wedding Center Pekanbaru Dengan Pendekatan Arsitektur Ekspresionis - Osli, Ranti; Aldy, Pedia; Susilawaty, Mira Dharma (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2020)
Pekanbaru wedding Center has the main function to support the wedding procession. Modernization that occurs in the city of Pekanbaru makes things practical, this tendency makes people prefer things that are considered practical but still effective and efficient, including the implementation of wedding receptions that want to be more efficient. The Pekanbaru Wedding Center is also provides supporting facilities such as salons and spas, wedding boutiques, jewelry stores, cake shops, photo studios, shopping centers, invitation shops, flower shops, catering and hotels in one area making it easier the bride and groom in meeting the needs of the wedding and in holding a wedding reception. that method uses is the Expressionist Architecture Approach which creates a building that expresses emotions and can be felt by people who see it so that it not only provides facilities that can enrich one's expression but also describes expressions in terms of architecture that creates the building. Expressionist architecture expresses expression through three physical elements of the building, namely the facade, the interior, the building plan, and the mass of the building. By the concept of Happy vibes is an atmosphere of happiness which is then described through the results of imagination and emotions which are then combined with several elements that influence the process of composition.keywords : Pekanbaru, Wedding Center, Expressionist Architecture